Political Orientation of Women Legislative Candidates in the 2019 Election: A Case Study of Elected Women Legislative Members of Padang City - Riri Izzatul Farmila; Indah Adi Putri; Jendrius (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2022)
The purpose of this study is to analyze the political orientation of 6 female legislative candidates who were elected in the 2019 election in Padang City using the political orientation theory by Almond & Verba which consists of cognitive political orientation, affective orientation, and evaluative orientation. This research is a qualitative research with data collection through direct interviews with female legislators in the city of Padang. Cognitive political orientation in which female legislators of the city of Padang conveyed the importance of the political parties that nominate, this was proven by several female legislators of the city of Padang. The number of female legislative members of the City is 6 people, in political orientation there are several ways that the female legislators of the City of Padang have. Affective political orientation is a feeling towards the political system, its roles, actors and appearances that make a person accept or reject a political system. The political orientation of the female legislators of the City of Padang is how to believe in the community that we are able to convey the aspirations of the community and can solve the problems that the community complains about. Evaluative political orientation Decisions and opinions about political objects that typically involve a combination of value standards and criteria with information and feelings. Affective orientation talks about women's feelings towards political aspects. While the evaluative component talks about the assessment of the political system and its parts. From the results of interviews with researchers, in general, the 6 female legislative members of Padang City who were elected had 3 political orientations, namely cognitive, affective, and evaluative. The tendency of affective orientation is reflected in statements of liking or disliking that say or show women's political parties based on the fulfillment of only 30% quotas. The tendency of evaluative orientation is the ability to evaluate the process that is being implemented, namely the election process and the process as a member of the legislature.